Pengaruh Pengelolaan Hutan Produksi terhadap Keragaman Jenis Plasma Nutfah Perairan - Reny Sawitri; Sofian Iskandar (Buletin Plasma Nutfah, 2006)
Management of forest production by application of Reduced Impact Logging (RIL) created crown opening by 13.3%, which was smaller compared with Conventional Logging (CNV) that caused crown opening by19.2%, and provided significant influence to water biodiversity. Availability of nutrient and essential minerals was better in RIL that was supported by high soluble residual or 95% higher and low velocity of river flow or 50% of surrounding CNV water. This physical condition showed significant difference to N and P ratio (N/P ratio) in RIL and CNV or 77.5 and 51.3. These values showed high content of nitrate of the water and it was in oligotropic type condition. Diversity Index of plankton in RIL was 1.754 and in CNV was 1.682 with each population density was 12,916 and 7,222 individuals/liter. The number of plankton had possitive correlation with N/P ratio (r = 0.9). In water catchment study area, there were found 28 fish species belonged to 20 genera and 8 families. The dominance families were Cyprinidae 57.14%, Bagridae 17.14%, and Anguillidae 7.14%. Most endemic fish species of Borneo were also found in both RIL and CNV water, however species with high relative frequency and density were found higher in RIL water. AbstrakPengelolaan hutan produksi dengan model penebangan Reduced Impact Logging (RIL) membuat pembukaan tajuk seluas 13,3% yang relatif lebih kecil dibandingkan dengan penebangan konvensional (CNV) dengan pembukaan tajuk seluas 19,2%, memberikan pengaruh yang berbeda terhadap keanekaragaman hayati perairan. Ketersediaan nutrisi dan hara penting yang lebih baik di perairan kawasan RIL ditunjang oleh tingginya residu terlarut 95% dan rendahnya kecepatan aliran air sungai 50% dari perairan sekitar CNV. Kondisi fisik perairan yang demikian menunjukkan perbedaan nyata terhadap perbandingan nitrat dan fosfat (N/P rasio) di RIL dan CNV, yaitu 77,5 dan 51,3. Nilai ini menunjukkan kadar nitrat perairan yang tinggi, dan perairan berada dalam tipe oligotropic. Indeks keragaman jenis plankton di RIL 1,754 dan di CNV 1,682 dengan populasi masing-masing 12.916 individu/liter dan 7.222 individu/ liter. Jumlah plankton ini berkorelasi positif dengan N/P rasio (r = 0,9). Di perairan sekitar DAS areal penelitian terdapat 28 jenis ikan tergolong kedalam 20 genera dan 8 famili. Famili dominan adalah Cyprinidae 57,14%, Bagridae 17,14%, dan Anguillidae 7,14%. Sebagian besar ikan jenis endemik Kalimantan terdapat pula di kedua perairan RIL dan CNV, tetapi jenis yang mempunyai kerapatan dan frekuensi relatif tinggi ditemukan lebih banyak di perairan RIL.